EMPOWERING THE IMPLEMENTATION OF SELF-RELIANCE BASED CHARACTER EDUCATION AT SMK SWASTA TELADAN TANAH JAWA - Herman Herman; Sherly Sherly; Dumaris E. Silalahi; Partohap Saut Raja Sihombing; Julyanthry Julyanthry; Muktar Bahruddin Panjaitan; Lydia Purba; Rianita Simamora; Bloner Sinurat; Sabar Dumayanti Sihombing (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
As we know that nowadays self-reliance is very important for the students in shaping their character. Lots of students are not mature because of they are not independence. The aim of this research is to empower the teachers’ understanding in implementing self-reliance based character education to the students. Methods used in this community service were socialization with PowerPoint presentation. Then sharing session with questions and answers to the presentation presented. This presentation was continued to case exposure with some reality conditions and group discussion. The location of this community service was at SMK Swasta Teladan Tanah Jawa in Simalungun Regency. Thirty-three teachers were the participants conducted on 7-8 January 2020. After collecting all the data, the researcher found that there are some results of how teachers can help to implement the self-reliance based character education such as: 1) to be active learners, 2) encouraging students in asking question when teaching and learning process for every subject, 3) teachers’ method of teaching, 4) integrating scout or boys’ brigade in the school, 5) students’ discipline to school policy, and 6) students’ freedom in using the internet as media for learning. Though there were problems in implementing the self-reliance based character education such as parents’ encouragement to school policy and teachers’ ability to implement the self-reliance in the subject, the researchers hope that this socialization can enlighten and empower teachers in implementing the self-reliance to the students for the brighter future of the students themselves and also for the advances of country.